Inducing optimal substitution between antibiotics under open access to the resource of antibiotic susceptibility. (15th May 2016) - Herrmann, Markus; Nkuiya, Bruno
Summary: This paper designs a bio‐economic model to examine the use of substitute antibiotic drugs (analogs) sold by an industry that has open access to the resource of the antibiotic class's susceptibility (treatment effectiveness). Antibiotics are characterized by different expected recovery rates and production costs, which in conjunction with the class's treatment susceptibility determines their relative effectiveness. Our analysis reveals that the high‐quality antibiotic drug loses its comparative advantage over time making the low‐quality drug the treatment of last resort in the market equilibrium and the social optimum when antibiotic susceptibility cannot replenish. However, when antibiotic susceptibility is renewable, both antibiotics may be used in the long run, and the comparative advantage of the high‐quality drug may be restored in the social optimum that allows lowering infection in the long run. We develop the optimal tax/subsidy scheme that would induce antibiotic producers under open access to behave optimally and account for the social cost of infection and value of antibiotic susceptibility. We show that the welfare loss associated with the uncorrected open‐access allocation is highest; when the resource of antibiotic susceptibility is non‐renewable, high morbidity costs are incurred by individuals, and low social discount rates apply. Copyright © 2016 John Wiley & Sons, Ltd.